Development of a Patient Decision Aid on the Choice of Diabetes Medication for Filipino Patients with Type 2 Diabetes Mellitus - Macalalad-Josue, Anna Angelica; Palileo-Villanueva, Lia Aileen; Sandoval, Mark Anthony; Panuda, Jose Paolo (Journal of the ASEAN Federation of Endocrine Societies, 2019)
Objective. To develop a locally adapted patient decision aid (PtDA) on treatment intensification among Filipino patients with Type 2 Diabetes Mellitus and to test the feasibility of using PtDAs in a low middle-income country. Methodology. A qualitative approach and an iterative process of development of a PtDA were employed for this study. We describe the process of developing a Filipino version of the Diabetes Medication Decision Aid. This PtDA was designed to help the patient choose the appropriate treatment intensification based on his own values and preferences, in consultation with his physician. The process involved decisional needs assessment through focus group discussions and key informant interviews, systematic literature review, iterative process of the development of a PtDA with clinical encounters (pilot testing), and preliminary field testing. Results. Decisional needs assessment revealed that Filipino patients are open to participate in shared decision-making if given the opportunity, including those with low socioeconomic status who likely have low health literacy. Physicians prefer to have visual aid tools to help them support their patient’s decision-making. A PtDA prototype of a set of flash cards in Filipino was created and revised in an iterative method. We developed a more visually appealing tool after inputs from the expert panel and patient advisory group. Its use during clinical encounters provided additional insights from patients and clinicians on how to improve the PtDA. Preliminary field testing showed that its use is feasible in the target patient population. Conclusion. Filipino patients, clinicians, and diabetes nurse educators have contributed to the creation of the first Filipino PtDA for diabetes treatment intensification. <center> </center>